Cryptic Connections : Spillovers between Crypto and Equity Markets - Iyer, Tara (International Monetary Fund, 2022)
Crypto assets have emerged as an increasingly popular asset class among retail and institutional investors. Although initially considered a fringe asset class, their increased adoption across countries-in emerging markets, in particular-amid bouts of extreme price volatility has raised concerns about their potential financial stability implications. This note examines the extent to which crypto assets have moved to the mainstream by estimating the potential for spillovers between crypto and equity markets in the United States and in emerging markets using daily data on price volatility and returns. The analysis suggests that crypto and equity markets have become increasingly interconnected across economies over time. Spillovers from price volatility of the oldest and most popular crypto asset, Bitcoin, to the S and P 500 and MSCI emerging markets indices have increased by about 12-16 percentage points since the onset of the COVID-19 pandemic, while those from its returns have increased by about 8-10 percentage points. Spillovers from the most traded stablecoin, Tether, to these indices have also increased by about 4-6 percentage points. In absolute terms, spillovers from Bitcoin to global equity markets are significant, explaining about 14-18 percent of the variation in equity price volatility and 8-10 percent of the variation in equity returns. These findings suggest that close monitoring of crypto asset markets and the adoption of appropriate regulatory policies are warranted to mitigate potential financial stability risks.